2013
DOI: 10.1007/s10578-013-0386-6
|View full text |Cite
|
Sign up to set email alerts
|

Modifying Adolescent Interpretation Biases Through Cognitive Training: Effects on Negative Affect and Stress Appraisals

Abstract: Adolescent anxiety is common, impairing and costly. Given the scale of adolescent anxiety and its impact, fresh innovations for therapy are in demand. Cognitive Bias Modification of Interpretations (CBM-I) studies of adults show that by training individuals to endorse benign interpretations of ambiguous situations can improve anxious mood-states particularly in response towards stress. While, these investigations have been partially extended to adolescents with success, inconsistent training effects on anxious… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 54 publications
(84 reference statements)
3
32
0
Order By: Relevance
“…While there are some emerging adult (MacLeod et al, 2009) and child data (Muris et al, 2008;Muris et al, 2009;Vassilopoulos et al, 2009) supporting the efficacy of cognitive training tasks as a treatment adjunct for anxiety and mood disorders, it is clear from our data that these tasks are also capable of impacting emotional well-being across adolescents too, and in particular not just adolescents with diagnoses (Lau et al, 2010;Lothmann et al, 2011;Telman et al, 2011). This makes it an appealing tool for prevention particularly in adolescence, which has been linked to a heightened vulnerability for anxiety disorders.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…While there are some emerging adult (MacLeod et al, 2009) and child data (Muris et al, 2008;Muris et al, 2009;Vassilopoulos et al, 2009) supporting the efficacy of cognitive training tasks as a treatment adjunct for anxiety and mood disorders, it is clear from our data that these tasks are also capable of impacting emotional well-being across adolescents too, and in particular not just adolescents with diagnoses (Lau et al, 2010;Lothmann et al, 2011;Telman et al, 2011). This makes it an appealing tool for prevention particularly in adolescence, which has been linked to a heightened vulnerability for anxiety disorders.…”
Section: Discussionmentioning
confidence: 68%
“…We have therefore adapted the adult training task for use in adolescents by the inclusion of age-appropriate training material (see Figure 1). Across three studies of over 160 adolescents aged 13-18 years, we have found robust training effects on subsequent interpretative style (Lau, Molyneaux, Telman, & Belli, 2010;Lothmann, Holmes, Chan, & Lau, 2011;Telman, Holmes, & Lau, 2011). However, mood effects associated with training have been less clear, with one study reporting reduced negative affect after positive training (Lothmann et al, 2011) and the other two finding reporting decreased positive affect (Lau et al, 2010) and increased negative affect in negatively-trained adolescents only.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…In addition to reducing anxiety symptoms in clinically anxious adolescents (Reuland & Teachman, 2014), CBM for interpretation bias in particular has been shown to reduce self-reported anxiety during psychological challenge (Lau, Belli, & Chopra, 2013) and life stress (Telman, Holmes, & Lau, 2013) in non-diagnosed youth samples.…”
Section: Cognitive Biases and Youth Anxietymentioning
confidence: 99%
“…Positive CBM-I has shown to increase mood [28][29][30] and has beneficial effects on appraisals of recent stressors [31] as well as on emotional vulnerability (i.e., responsiveness to a negative moodor stress induction) [26,30]. Moreover, encouraging healthy participants to attain positive interpretations -compared to negative interpretations -reduces the chance of experiencing depressive intrusions following a stressor [32].…”
Section: Interpretation Bias Modificationmentioning
confidence: 99%